Pengaruh Informasi Akuntansi, Informasi Non Akuntansi, Manajemen Resiko Pembiayaan terhadap Keputusan Pemberian Pembiayaan yang dimoderasikan Pengalaman pada PT. Bank Riau Kepri Syariah Wilayah Kepri - Maiza Tri Handayani; Chablullah Wibisono; Bambang Satriawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to test accounting information, non-accounting information, financing risk management on financing decisions moderated by experience. This research approach uses associative research. The population in this study was 128 people who conducted financing analysis in the network of office units of PT. Bank Riau Kepri Syariah (Perseroda) in the Riau Islands Region. The sampling technique in this study used saturated samples and obtained a sample of 128 respondents. The data collection technique used a questionnaire with a Likert scale. The data analysis method used is Partial Least Square (PLS) using SmartPLS 3.0 Software. The results of this study indicate that accounting information, non-accounting information and risk management have a positive and significant effect on financing decisions, Experience moderates the effect of accounting information negatively and insignificantly on financing decisions with moderation qualifications as predictors, Experience moderates the effect of non-accounting information positively and significantly on financing decisions, with moderation qualifications as quasi moderation (pseudo moderation). Experience moderates the influence of financing risk management negatively and insignificantly on the Decision to Grant Financing with the qualification of moderation as a predictor